Developing a safety climate factor model in construction research and practice: A systematic review identifying future directions for research. Issue 6 (25th July 2018) - Newaz, Mohammad Tanvi; Davis, Peter Rex; Jefferies, Marcus; Pillay, Manikam
Abstract : Purpose: Safety climate and its impact on safety performance is well established; however, researchers in this field suggest that the absence of a common assessment framework is a reflection of the state of development of this concept. The purpose of this paper is to propose a five-factor model that can be used to diagnose and measure safety climate in construction safety research and practice. Design/methodology/approach: A systematic review was adopted, and following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, 574 articles were selected at the start of the study based on a developed review protocol for investigating safety climate factors. While examining the factor analysis of different studies, data reliability and data validity of the individual research findings were considered and frequency of factors uploaded was used to determine the significance as a quantitative measure to develop the ranking of safety climate factors. Findings: The review identified that, from the established measures of safety climate in construction, there is little uniformity on factor importance. However, management commitment safety system role of the supervisor; workers' involvement and group safety climate were found to be the most common across the studies reviewed. It is proposed these factors are used to inform a five-factor model for investigating safety climate in the construction industry. Originality/value: The findings of this study will motivate researchers and practitioners in safety to use the five-factor safety climate model presented in this paper and test it to develop a common factor structure for the construction industry. The fact that the model is comprised of five factors makes it easier to be used and implemented by small-to medium-sized construction companies, therefore enhancing its potential use.